-3y+15=24
-3y=9
3y=-9
y=-3
Answer: The 60th term of the arithmetic sequence -29, -49, -69, … is -1209.
Step-by-step explanation:
The given arithmetic sequence is -29, -49, -69, …
To find the 60th term of this sequence, we need to use the formula for the nth term of an arithmetic sequence:
a_n = a_1 + (n - 1)d
where a_n is the nth term of the sequence, a_1 is the first term of the sequence, n is the number of terms in the sequence, and d is the common difference between consecutive terms.
In this case, a_1 = -29 and d = -20 (since each term is 20 less than the previous term). We want to find a_60, so we substitute n = 60 into the formula:
a_60 = -29 + (60 - 1)(-20) = -29 + 59(-20) = -29 - 1180 = -1209
Therefore, the 60th term of the arithmetic sequence -29, -49, -69, … is -1209.
Please let me know if you have any other questions!
Answer:
5 plus i square root of 11
Step-by-step explanation:
I got right on the test.